1972
DOI: 10.1007/bf00822760
|View full text |Cite
|
Sign up to set email alerts
|

Some models describing the distribution of eggs of the parasitePseudeucoila bochei (Hym., Cynip.) over its hosts, larvae ofDrosophila melanogaster

Abstract: Ovipositing females of the cynipid waspPseudeucoila bochei discriminate between parasitized and unparasitized hosts, which results in a far more uniform distribution of eggs over the hosts than would be obtained if oviposition were random (Fig. 1,a -f).For the description of the distributions a few models were worked out, which rest on the assumption that the hosts are probed at random. The total number of effective probes made in a larva during the experiment is a random variable with a Poisson distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
11

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 15 publications
1
59
1
11
Order By: Relevance
“…Under the conditions used, many larvae contained more than one egg; the highest number found was seven. Superparasitism occurs in Leptopilina but only one larva successfully continues development so one adult wasp emerges from each Drosophila pupal case (14).…”
Section: Methodsmentioning
confidence: 99%
“…Under the conditions used, many larvae contained more than one egg; the highest number found was seven. Superparasitism occurs in Leptopilina but only one larva successfully continues development so one adult wasp emerges from each Drosophila pupal case (14).…”
Section: Methodsmentioning
confidence: 99%
“…Where oviposition is not entirely suppressed by MP, females may still lay smaller clutches (Ikawa & Okabe, 1985;Papaj et al, 1990). The extent to which clutch size is reduced in a previously utilized host has been shown in gregarious parasitoids to be a function of the number of eggs that were deposited previously in that host (Bakker et al, 1972;van Dijken & Waage, 1987).…”
Section: Effects Of Mps On Female Behaviormentioning
confidence: 99%
“…A similar correlation between marking time and clutch size deposited within a host has also been found for the gregarious wasp, Telenomus fariai (Bosque & Rabinovich, 1979). In other cases in which females make a graded assessment of level of infestation, the underlying mechanism has not been conclusively established (Bakker et al, 1972(Bakker et al, , 1990van Lenteren & Debach, 1981;van Dijken & Waage, 1987).…”
Section: Benefits Of Marking Hostsmentioning
confidence: 99%
“…An aborted ovipositional attempt could result in host marking yet leave the potential host available for attack. Bakker et al (1972) developed a model describing egg distribution based on host discrimination. These authors reported that a model where the chance of an egg being deposited decreased as the number of eggs increased provided the best fit.…”
Section: Host Identificationmentioning
confidence: 99%